Diversifikasi Produk Kerajinan Bambu Di Desa Halunuk Kecamatan Loksado Hulu Sungai Selatan - Hafizianor hafizianor; asysyifa asysyifa (Universitas Lambung Mangkurat, 2023)
Abstract.KTH Wana Sejahtera (partners) is a farmer group located in Halunuk Village, Loksado District, Hulu Sungai Selatan Regency which was formed in the context of a social forestry program in an effort to increase the income of the Halunuk Village community, this group raises bamboo-based handicrafts as a business that the group will develop because considered to have a fairly good market opportunity. The implementing team for the 2022 Lecturer Mandatory Service Program seeks to provide solutions to partners, namely by providing knowledge and information about the diversification of woven bamboo products. This activity is expected to support the government's efforts to improve the welfare of people living around forests, thereby reducing their dependence on forests. The problem faced by partners is the lack of skills and innovation in producing woven bamboo products, this is because the local community is only able to make woven bamboo products in the form of Lanjung or Butah and lack of knowledge about the use of social media as a means of promotion in the process of marketing the products they produce. . The method of activity is in the form of counseling, training in making woven bamboo, assistance to activity partners and program evaluation. The results of the counseling and training activities showed that 80% of the participants were able to practice the product manufacturing techniques exemplified by the resource persons. The outputs produced in the Mandatory Serving Lecturer Program activities are bamboo handicraft products, publications in the mass media, activity videos on YouTube channels and scientific articles.Keywords: bamboo, product diversification, handicraft